Parvovirus B19 in Morocco: Seroprevalence of Immunoglobulin G Antibody in Pregnant Women in Marrakesh - Majda Bouraddane; Karima Warda; Youssef Elkamouni; Lamiae Arsalane; Said Zouhair (IMR Press, 2023)
Background: Parvovirus B19 (B19V) infection is ever-present and contagious. It is acquired during childhood and adolescence, but can occur at any age. B19V infection occurs in endemic epidemic mode in temperate zones in winter and spring. B19V infections, although often asymptomatic in pregnant women, can be responsible for hydrop fetalis, fetal anemia, and death in utero. This study will evaluate the seroprevalence of immunoglobulin G (IgG) antiparvovirus in pregnant women in Marrakesh city in Morocco, and to find out the possible risk factors associated with B19V infections. Methods: We randomly selected 100 pregnant women from the Zerktouni hospital in Marrakesh. Socio-demographic characteristics and background were collected using a questionnaire. Serologic tests were carried out by searching for immunoglobulin G antibodies via the ParvovirusVirclia® IgG Chemiluminescencemonotest kits (Vircell Microbiologist, Granada, Spain) at the Bacteriology-Virology laboratory of the Avicenna Military Hospital in Marrakesh. Results: The median age of study participants was 27 (interquartile range (IQR): 17-43) years. Of 100 pregnant women 8%, 38% and 54% were in the first, second and third trimester respectively. The majority 96% of women were from urban areas. Nineteen percent (19%) of them had a history of spontaneous abortion. Of 100 pregnant women, the overall prevalence of IgG was 51 (51%). The average age of participants with positive serology was 26.45 years, and the mean age of those with negative serology was 28.98 years. The immunity against the virus was higher in young pregnant women. Twenty five (25%) women tested positive for B19V antibodies in the third trimester of pregnancy, implying immunity for the virus. The results of logistic regression showed insignificant association between the prevalence of B19V IgG antibodies and the demographic and obstetrical factors except for the having a child under 6 years factor (χ2 = 12.33, p = 0.001). Conclusions: Infection with B19V remains important in pregnant women in our region and virological diagnosis must be sought before any suggestive context.